2018
DOI: 10.1111/jsr.12697
|View full text |Cite
|
Sign up to set email alerts
|

The nature of delayed dream incorporation (‘dream‐lag effect’): Personally significant events persist, but not major daily activities or concerns

Abstract: SummaryIncorporation of details from waking life events into rapid eye movement (REM) sleep dreams has been found to be highest on the 2 nights after, and then 5-7 nights after, the event. These are termed, respectively, the day-residue and dreamlag effects. This study is the first to categorize types of waking life experiences and compare their incorporation into dreams across multiple successive nights. Thirtyeight participants completed a daily diary each evening and a dream diary each morning for 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Since daily perceived stress did not predict the dream valence experienced on the subsequent night, models testing for potential a dream-lag effect (i.e., increased incorporation in dreams of events having occurred 5–7 days prior to the dream) 52,53 were also computed post hoc. Separate datasets pairing daily perceived stress levels from previous days (i.e., two to seven days prior to recalled dreams) with reported valence of subsequently recalled dream were generated.…”
Section: Resultsmentioning
confidence: 99%
“…Since daily perceived stress did not predict the dream valence experienced on the subsequent night, models testing for potential a dream-lag effect (i.e., increased incorporation in dreams of events having occurred 5–7 days prior to the dream) 52,53 were also computed post hoc. Separate datasets pairing daily perceived stress levels from previous days (i.e., two to seven days prior to recalled dreams) with reported valence of subsequently recalled dream were generated.…”
Section: Resultsmentioning
confidence: 99%
“…Another plausible hypothesis refers to the possibility that waking emotions are expressed in dreams across a different time span than those measured in our study. For instance, in analogy with data on the delayed incorporation of waking events in dreams [ 21 , 22 , 23 ], emotions experienced on a certain day could be reflected in the dream with a few days’ lag. However, our exploratory analysis on the participants reporting their dream with a few days’ delay from the beginning of data collection (and thus providing more than one WAKE24hr scale) does not support this idea.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the possibilities are multiplied when considering emotional valence: in fact, a common mechanism can be hypothesized for the expression in dreams of both positive and negative emotions (e.g., one of the mechanisms proposed above), or else, they could undergo different pathways (e.g., positive emotions dominate in dreams when negative ones are prevalent during wake and vice versa, etc.). Finally, different hypotheses may also be put forward regarding the time span over which these mechanisms unfold: for instance, daytime emotions may be processed in the immediately subsequent dream or with a few days’ lag (in analogy with literature on the “dream lag” and “day-residue” effect [ 21 , 22 , 23 ]); or each dream may process emotions generated and/or experienced during wider daytime spans (e.g., the last few weeks, the general “time period”), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Dreaming is a universal experience that occurs during sleep. There is evidence for a 7-day U-shaped timescale of incorporation of memories of experiences when awake into dreams, in which events from 1 or 2 days before the dream, and from 5 to 7 days before the dream, are preferentially incorporated into dream content (e.g., Nielsen and Powell, 1992;Nielsen et al, 2004;Blagrove et al, 2011;van Rijn et al, 2015;Eichenlaub et al, 2019). The recent incorporations are termed the day-residue effect, and the delayed incorporations the dream-lag effect.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, external judges who do not know participants' information rated correlations between participants' waking events and dream reports. Evidence showed that when compared with the independent-judge method, the self-report method has the advantage of studying the dream-lag effect (for a discussion, see the introduction section in Eichenlaub et al, 2019). However, in our opinion, when a study aims to explore whether some personality traits can affect conscious experiences' incorporation into dreams, the independent-judge method is more suitable than the self-report method.…”
Section: Introductionmentioning
confidence: 99%